Analysis of Accounting Application in 'Dokter Interior' Using Microsoft Access - Iwan Suhardjo; Salmayani Salmayani (Universitas Internasional Batam, 2023)
In this paper, readers are expected to understand that in the application of calculations using an accounting system to Micro, Small, and Medium Enterprises (MSMEs) can be considered important. The purpose of helping partners is to create and improve the existing transaction system in the 'Interior Doctor'. This research took place from September to December using qualitative methods. The system created by the authors uses Microsoft Access, where data is collected gradually during the study. According to the final results, there are losses that occur after the financial statements are successfully made. The losses estimated per month are not much, but of course they cannot be left alone later by partners. This makes it even stronger, that small business owners, should not neglect the recording of financial statements that occur whenever there is a transaction.